2007
DOI: 10.4141/cjps06013
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of high seeding rates to increase grain yield of winter wheat and winter triticale in southern Alberta

Abstract: . 2007. Efficacy of high seeding rates to increase grain yield of winter wheat and winter triticale in southern Alberta. Can. J. Plant Sci. 87: 503-507. Field trials were conducted for 3 yr (2002/2003 to 2004/2005) at three locations in southern Alberta to determine the impact of seeding rate and opener type on plant stand and grain yield of winter wheat (Triticum aestivum L.) and winter triticale (× Triticosecale Wittmack). Responses were determined for an optimum date of seeding in early to mid-September an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…For fall and spring density, respectively, a curvilinear and linear stand percentage decrease occurred as seeding rate increased. Reduced stand percentage is consistent with another study conducted in Alberta where spring stand percentage decreased as seeding rate increased (McKenzie et al, 2007).…”
Section: Winter Wheat Stand Establishmentsupporting
confidence: 80%
See 1 more Smart Citation
“…For fall and spring density, respectively, a curvilinear and linear stand percentage decrease occurred as seeding rate increased. Reduced stand percentage is consistent with another study conducted in Alberta where spring stand percentage decreased as seeding rate increased (McKenzie et al, 2007).…”
Section: Winter Wheat Stand Establishmentsupporting
confidence: 80%
“…Although their results were reported on a volume basis, which can vary significantly with kernel size, shape, and weight, the rate was approximately twice that of earlier recommendations. McKenzie et al (2007) reported that increasing seeding rates to achieve a plant density of 350 plants m -2 was ideal for conditions in southern Alberta, particularly if seeding dates were delayed past the optimal window of sowing; that is, early-to mid-September. Th e greatest response to seeding rate was observed in conditions where moisture was not a limiting factor (Tompkins et al, 1991).…”
mentioning
confidence: 99%
“…Plant density was significantly affected by row spacing and seeding rate, but not by the interaction of row spacing and seeding rate ( depend on seeding density, similarly to other cereal crops (McKenzie et al 2007). Further study is required on seedling establishment of corn, particularly in environments that are not conducive to full and rapid emergence of corn seedlings.…”
mentioning
confidence: 89%
“…Fowler (1986) also used plant densities similar to or slightly less than these recommendations. However, more recent research (Beres et al, 2010;Lafond and Gan, 1999;McKenzie et al, 2007) concluded that earlier recommendations from previous research and farmer practices that involved a sowing density around 200 to 250 seeds m -2 did not provide a consistent plant density nor could it readily achieve the yield potential of new cultivars. Adoption of more modern research recommendations has resulted in an increase in the industry standard practice to 450 seeds m -2 (Beres et al, 2010).…”
Section: Core Ideasmentioning
confidence: 99%